ENGLISH WRITING SKILL ANALYSIS OF FIRST YEAR INDONESIAN TERTIARY STUDENTS IN A UNIVERSITY IN BANDUNG - Yuliana, Dian; Imperiani, Ernie D.A.; Kurniawan, Eri (Universitas Pendidikan Indonesia, 2016)
Abstract This article reports a study on English writing skill of Indonesian tertiary students. The purpose of the study is to examine students’ initial ability in writing English compositions. The subjects of the study are 22 university students in their first year at English Language and Literature study program at one university in Bandung. The data are taken from students’ descriptive essays written in the classroom. The texts are then analyzed based on writing rubrics developed by Lane and Lange (1999) to see the recurrent global and local errors, supported by analytic writing rubrics proposed by Jacobs et al. (1981) to see the students’ writing ability in general. The results of the study show that the recurrent errors made in twenty-two English descriptive essays are singular/plural nouns for local errors and sentence structure for global errors. In terms of analytic view, errors in language use are the most frequent errors made by the students. The findings provide useful information for constructing teaching materials for English writing in this study program.Keywords: writing skill, descriptive text, composition scoring technique, analytic scoring technique, global and local errors. Abstrak Artikel ini melaporkan hasil kajian mengenai keterampilan menulis bahasa Inggris mahasiswa. Tujuan penelitian ini adalah untuk memotret kemampuan awal menulis mahasiswa dalam bahasa Inggris. Adapun subjek penelitian adalah 22 orang mahasiswa tingkat I di Program Studi Bahasa dan Sastra Inggris, di sebuah universitas di Bandung yang dipilih untuk mengetahui kemampuan awal mereka. Data diperoleh melalui karangan deskriptif yang ditulis di kelas.Teks dianalisis dengan menggunakan rubrik penilaian yang dikembangkan oleh Lane and Lange (1999) untuk tataran global dan lokal (global and local errors); dan rubrik penilaian analitik yang dikembangkan oleh Jacobs (1981) untuk melihat keterampilan menulis mahasiswa secara umum. Analisis data menunjukkan bahwa kesalahan yang paling banyak dilakukan mahasiswa pada tataran lokal terkait pemarka nomina tunggal dan jamak (singular/plural nouns), sedangkan pada tataran global, kesalahan pada struktur kalimat (sentence structure) merupakan kesalahan yang paling sering dilakukan oleh mahasiswa. Dari sisi analitik, kesalahan pada penggunaan bahasa merupakan kesalahan yang paling sering ditemukan dalam kebanyakan tulisan mahasiswa.Hasil temuan ini diharapkan dapat memberikan masukan bagi penyusunan bahan ajar matakuliah menulis di lingkungan program studi. Kata kunci: keterampilan menulis, teks deskriptif, teknik penilaian tulisan, teknik penilaian analitik, kesalahan global dan local.